Influence of bone adaptation on tendon-to-bone healing in bone tunnel after anterior cruciate ligament reconstruction in a rabbit model - Wen, Chun-Yi; Qin, Ling; Lee, Kwong-Man; Wan-Nar Wong, Margaret; Chan, Kai-Ming (Journal of orthopaedic research, 2009)
Anterior cruciate ligament (ACL) reconstruction with placement of grafted tendon in bone tunnel is a common surgical procedure. Bone tunnel creation may result in stress shielding of postero‐lateral regions of tibial tunnel. The present study was designed to characterize the changes of peri‐graft bone and compare with tendon‐to‐bone (T‐B) healing in spatial and temporal manners after ACL reconstruction in rabbit. Surgical reconstruction using digital extensor tendon in bone tunnel was performed on 48 rabbits. Twelve rabbits were sacrificed at 0, 2, 6, and 12 weeks postoperatively for radiological and histological examinations. Bone mass and microarchitecture at the anterior, posterior, medial, and lateral regions of tunnel wall at distal femur and proximal tibia were evaluated. Using peripheral quantitative computed tomography, a 26, 22, and 42% decrease in bone mineral density (BMD) relative to baseline was present in the medial region of the femoral tunnel and the posterior and lateral regions of the tibial tunnel, respectively, at week 12 postoperatively (p < 0.05). It was accompanied by a decrease in trabecular number and increase in trabecular spacing, the shift of platelike to rodlike trabeculae, and loss of anisotropy under micro‐computed tomography evaluation. This finding was echoed by histology showing increased osteoclastic activities and poor T‐B healing in these regions. In conclusion, the postoperative bone loss and associated poor T‐B healing was region‐dependent, which may result from adaptive changes after tunnel creation. © 2009 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 27:1447–1456, 2009